Phytochemical and Behavioral Assessment of Guiera senegalensis for Antidepressant Activity - Muazu, Ibrahim Khaleel; Nasir, Aisha Balanmalam; Tahir, Albashir (Sciences of Phytochemistry, 2025)
Depression is a prevalent and debilitating mental disorder that significantly affects global health and quality of life. Conventional pharmacological treatments have adverse effects, necessitating the search for alternative therapies. This study aimed to evaluate the potential antidepressant activity of the ethanol leaf extract of Guiera senegalensis in Wistar rats. Phytochemical screening was performed to identify bioactive compounds in the extract. Acute toxicity was assessed following OECD guidelines, with doses up to 5000 mg/kg. The antidepressant activity was evaluated using the Forced Swim Test (FST) and Tail Suspension Test (TST). Experimental groups received extract doses of 25, 50, and 100 mg/kg, with control groups receiving normal saline and reference groups treated with imipramine (10 mg/kg). Statistical analyses were conducted using one-way ANOVA with Dunnett’s post hoc test. Phytochemical analysis revealed the presence of flavonoids, tannins, and saponins, which are known for their neuropharmacological properties. Acute toxicity testing showed no mortality at 5000 mg/kg, indicating a high safety profile. Behavioral assessments demonstrated that the extract significantly reduced immobility time in the FST and TST at doses of 50 and 100 mg/kg (p < 0.05), suggesting antidepressant activity. The ethanol leaf extract of G. senegalensis exhibits both antidepressant effects in animal models, supporting its traditional use in managing mood disorders. The presence of bioactive compounds suggests a pharmacological basis for its efficacy. Further research is needed to elucidate its mechanisms of action and assess its long-term safety.